Parenting stress among mothers of children with different physical, mental, and psychological problems - Awat Feizi; Badroddin Najmi; Aseih Salesi; Maryam Chorami; Rezvan Hoveidafar (Journal of Research in Medical Sciences, 2014)
Background: Parents of children with developmental problems are always bearing a load of stress. The aim of this study is to compare the stress in mothers of children with different disabilities to each other, considering their demographic background. Materials and Methods: This was a cross-sectional study conducted in Isfahan, Iran during 2012 on 285 mothers of 6-12 years old children with chronic physical disease, psychological disorder, and sensory-motor and mental problems. Abedin′s parenting stress questionnaire was used and obtained data were analyzed using multivariate analysis of variance or covariance as appropriate. Results: Mothers of children with sensory-motor mental and chronic physical problems experience more stress than mothers of children with psychological disorders (P < 0.05). The stress score of mothers of children with psychological disorders was lower than the other two groups. Also there was a significant difference between the score of mothers of children with chronic physical problems and mothers of children with psychological disorders regarding parent-child dysfunctional interaction (P < 0.01). A significant difference was observed in terms of stress among mothers of children with sensory-motor mental problems with different number of children (P < 0.05); also mothers of children with chronic physical problems in different levels of education have experienced different levels of parenting stress (P < 0.05) Conclusion: Due to high level of parenting stress among our studied samples, special education and early intervention are needed for parents in our study population in order to deepening their diagnostic knowledge and professional consultation on stress management